Screening of hybridoma cell lines secreting monoclonal antibodies specific for staphylococcal enterotoxin B (SEB) derived from Staphylococcus aureus - Minh, Nghiêm Ngọc; Thu, Nguyễn Thị Hoài; Linh, Phạm Thùy; Dương, Thân Đức; Hằng, Vũ Thị Thu; Phan, Lê Văn (Vietnam Journal of Biotechnology, 2016)
Staphylococcus aureus (S. aureus) produces 11 types of toxins and more than 20 different Staphylococcal enterotoxins (SEs), including SEA to SEE, SEG to SER and SEU. Among them, enterotoxin type B (Staphylococcal enterotoxin B - SEB) is quite heat stable and causes gastrointestinal diseases in food poisoning. The symptoms of SEB intoxication begin with the onset of sudden fever, about 40oC to 41oC, chills, headache, muscle aches and dry cough. Some patients feel shortness of breath and chest pain. Although SEB is not considered lethal, high level of exposure can lead to shock and death. Therefore, a nontoxic SEB recombinant antigen was produced to immunize mice to create B lymphocytes. Myeloma cells were fused with the B lymphocytes to generate hybridoma lines. The screening of monoclonal antibodies for the SEB antigen was determined by ELISA and Western blot tests. This study demonstrates that an SEB recombinant antigen can immunize a response against SEB in BALB/c mice. The production of monoclonal antibodies will be used to make a rapid detection strip for SEB based on immunochromatography.